2018
DOI: 10.1111/inm.12527
|View full text |Cite
|
Sign up to set email alerts
|

Combining e‐mental health intervention development with human computer interaction (HCI) design to enhance technology‐facilitated recovery for people with depression and/or anxiety conditions: An integrative literature review

Abstract: Computer scientists contend that understanding human computer interaction (HCI) is an important factor in developing successful computer user experiences. Mental health professionals across a range of disciplines are increasingly developing and implementing Internet-based treatments for people with a variety of mental health conditions. Many therapeutic and economic benefits are associated with technology-enabled treatments for a range of mental health disorders. Despite this, the role of HCI and associated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 50 publications
(132 reference statements)
1
56
0
Order By: Relevance
“…Aesthetics in the context of interface design has been described as the visual appearance of the interface, as it conforms to design principles such as symmetry and balance [39], and the complexity of the interface [40,41]. Furthermore, when designing for usability it is important to make considerations as to the users' preferences concerning layout features such as images, colors, text quantity, and font size and color [42], moreover, studies have shown a correlation between products that are aesthetically pleasing and their usability [43,44].…”
Section: Visual Appearance and Usabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Aesthetics in the context of interface design has been described as the visual appearance of the interface, as it conforms to design principles such as symmetry and balance [39], and the complexity of the interface [40,41]. Furthermore, when designing for usability it is important to make considerations as to the users' preferences concerning layout features such as images, colors, text quantity, and font size and color [42], moreover, studies have shown a correlation between products that are aesthetically pleasing and their usability [43,44].…”
Section: Visual Appearance and Usabilitymentioning
confidence: 99%
“…Consider the end-users cognitive level of functioning [29]) Computer literacy Consider the end-users level of computer literacy Visual appearance [42] Use appealing colors and design…”
Section: Personalizationmentioning
confidence: 99%
“…Despite this, mHealth apps are still disabled within weeks of download [38], suggesting that extensive digital phenotyping efforts are insufficient for optimizing user engagement [39,40]. Assessment of user preferences increases mHealth treatment engagement [41], but populations perceived as difficult to engage, such as individuals with psychiatric illnesses, are often excluded from treatment adaptation research, primarily due to concerns about the reliability of self-report measures due to cognitive limitations [42]. However, it is exactly these cognitive limitations that necessitate the need for usability and preference testing [41,43].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Along similar lines, online interventions for patients with abnormal grief are supported by studies that have demonstrated their efficacy. However, one of the main problems that have been observed in terms of online interventions aimed at treating depression and anxiety symptoms is the broad description of the theoretical content, and the poor description of the relevant characteristics of the human-computer interaction design (Søgaard and Wilson, 2019). For example, a study published in 2017, identified that there is a lack of research offering qualitative data about the subjective User Experience (UX) of young people using interventions for depression, such as social network based (Santesteban-Echarri et al, 2017).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Among the aspects of human-computer interaction design, the concept of universal design aims to design interactions with digital tools which are aesthetically pleasing, and at the same time ensures that the tool can be used by all participants, regardless of their age, ability, or status (Søgaard and Wilson, 2019). It is relevant to note that older adults are interested in using technology to take care of their mental health and this form of intervention is feasible and reliable for them (Figueroa and Aguilera, 2020).…”
Section: Introduction Backgroundmentioning
confidence: 99%